Protecting paid domestic workers under lockdown: Latin American strategies during the COVID-19 pandemic. (2nd January 2022) - Poblete, Lorena
ABSTRACT: Most domestic workers in Latin America earn low wages and have no formal contract. When the COVID-19 pandemic began, the position of these workers became even more precarious as working time was reduced for many, and as a result, incomes declined. Many other workers suffered suspensions without pay or redundancy without severance. Governments across the region thus sought to develop new strategies to guarantee domestic workers' income. Taking a comparative perspective, the paper aims to understand a variety of government responses to the domestic work issue during the COVID-19 pandemic in four Latin American countries (Argentina, Chile, Colombia and Paraguay). An analysis of all regulations enacted during the first nine months of the pandemic leads into a discussion of the primary dilemma states faced: determining whether domestic workers could be protected as workers or as a segment of the working poor.